2022
DOI: 10.21037/atm-22-1730
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for C5 palsy following the posterior spinal process-splitting laminoplasty for cervical ossification of the posterior longitudinal ligament: a case control study

Abstract: Background: Postoperative C 5 palsy is a common complication of laminoplasty for cervical ossification of the posterior longitudinal ligament (C-OPLL), although there are several hypotheses regarding its etiology, the exact pathomechanism for this undesirable event remain unclear. The aim of this study was to review clinical and imaging findings in patients with C 5 palsy and to propose potential risk factors for this complication.Methods: A total of 220 consecutive patients who had undergone posterior spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The incidences of C5 palsy after EOLP and CLF reported in this study are lower than what has typically been reported in the literature. 17,18 A similar incidence of C5 palsy was seen with CLF (2.7%) with no side preference. The overall complication rate and severity were higher in the CLF group, as was the age distribution in this nonrandomized series.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The incidences of C5 palsy after EOLP and CLF reported in this study are lower than what has typically been reported in the literature. 17,18 A similar incidence of C5 palsy was seen with CLF (2.7%) with no side preference. The overall complication rate and severity were higher in the CLF group, as was the age distribution in this nonrandomized series.…”
Section: Discussionmentioning
confidence: 60%
“…A study by Uzunoglu et al 17 revealed that patients with OPLL had a higher incidence of C5 palsy (17.3%) than those with other clinical diagnoses prior to surgery in the rest of the study, which had a combined incidence of 12.4%. EOLP for OPLL was also found to have a higher rate of C5 palsy in other studies, including those by Khuyagbaatar et al, 22 Wang et al, 16 Li et al, 18 and Deshpande et al 19 Several causative factors for C5 palsy have been suggested, such as iatrogenic nerve damage, thermal damage during drilling of the bone, stretching of nerve roots due to displacement of the spinal cord, compression of the root within the stenotic foramina, and ischemic-reperfusion injury of the spinal cord; however, the exact pathophysiology has yet to be identified. 14,15,17,[20][21][22] In this study, we focused on the question as to whether hinge sidedness is important in determining the laterality of C5 palsy.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…The following outcomes were evaluated: operative time, blood loss, neurological state (assessed by the Japanese Orthopaedic Association [JOA] score), and JOA score recovery rate ([postoperative JOA score − preoperative JOA score]/[17 − preoperative JOA score] × 100%) [ 11 ]. All surgery-related events that occurred within 30 days after the operation were defined as perioperative complications, among which C5 palsy was defined as deltoid and biceps motor weakness, paresthesia, or numbness in the distribution of the C5 nerve root without deterioration of myelopathic symptoms [ 12 ].…”
Section: Methodsmentioning
confidence: 99%